Physiological adjustment to postnatal growth trajectories in healthy preterm infants - Rochow, Niels; Raja, Preeya; Liu, Kai; Fenton, Tanis; Landau-Crangle, Erin; Göttler, Susanne; Jahn, Andrea; Lee, Sauyoung; Seigel, Sandra; Campbell, Douglas; Heckmann, Matthias; Pöschl, Johannes; et al. (Pediatric research, 2016)
International guidelines suggest that growth of preterm infants should match intrauterine rates. However, the trajectory for extrauterine growth may deviate from the birth percentile due to an irreversible, physiological loss of extracellular fluid during postnatal adaptation to extrauterine conditions. To which “new” physiological growth trajectory preterm infants should adjust to after completed postnatal adaptation is unknown. This study analyzes the postnatal growth trajectories of healthy preterm infants using prospective criteria defining minimal support, as a model for physiological adaptation. International, multi-center, longitudinal, observational study at five neonatal intensive care units (NICUs). Daily weights until day of life (DoL) 21 of infants with undisturbed postnatal adaptation were analyzed (gestational ages: (i) 25-29 wk, (ii) 30-34 wk). 981 out of 3,703 admitted infants included. Maximum weight loss was 11% (i) and 7% (ii) by DoL 5, birth weight regained by DoL 15 (i) and 13 (ii). Infants transitioned to growth trajectories parallel to Fenton chart percentiles, 0.8 z-scores below their birth percentiles. The new trajectory after completed postnatal adaptation could be predicted for DoL 21 with R2 = 0.96. This study provides a robust estimate for physiological growth trajectories of infants after undisturbed postnatal adaptation. In the future, the concept of a target postnatal trajectory during NICU care may be useful.
Gesehen am 30.04.2020